Mastering Vocabulary Through Brainstorming Game In Eight Grade Students At MTS Al- Wasliyah Lubuk Pakam 2022/2023 - Selfitrida A. Yani (Universitas Dharmawangsa, 2024)
The study find out that teaching vocabulary through brainstorming game could develop the students' ability in using vocabulary, especially for students in Eighth grade MTs.Al-Wasliyah Lubuk Pakam in the extend 85.18% . After analyzing the data, it was found out the students' ability in using vocabulary got improvement through brainstorming game. The result of the analyzing the data showed that there was an improving on the students' ability in mastering vocabulary from each cycles. It was showed from the mean of pre-test was 39,62. Where, there were 9 students got success score criteria or it was only 33.33% and 18 students got unsuccess or it was 66,67 %. After doing cycle I through brainstorming game, there was an improving of the result of the students' mean was 58.14. Where, 15 students got success criteria score or it was only 55.56% and 12 students got unsuccess criteria score or it was 44.44%. Then, doing repairing for second cycle after reflection on the first cycle, there was improving of students' mean was 88.89. Where, 23 students' got success criteria score or it was 85,18%. In other words, the students' ability in mastering vocabulary was improved. And based on interviewed, observation sheet, diary notes and documentation, it showed that the expression and excitement of the students were also improved.